PROSEDUR PENGUJIAN SUBSTANTIF AKUN PENDAPATAN PT XYZ OLEH KANTOR AKUNTAN PUBLIK JOACHIM ADHI PITER POLTAK DAN REKAN - Muhamad Abdul Ghofur (2022)
Substantive testing is the auditing stage by the auditor as the testing stage or the detection of misstatements which directly affect the authenticity of the accounts in the financial statements. Income is profit or profit from parties who are trying to fulfill their life by putting in capital and being prepared for the risks they will face in the future. The main purpose of this final project is to identify the revenue substantive testing process implemented by the Public Accounting Firm Joachim Adhi Piter Poltak and Partners and to detect its strengths and weaknesses. Information from the desired data is obtained by observing the process from the stages and evidence of the substantive testing process that is utilized or used by the Public Accounting Firm of Joachim Adhi Piter Poltak & Partners. The substantive test aims to identify and ensure that the revenue account of PT XYZ for the 2021 period has been created and presented fairly and no misstatements were found.